Enhancing access to genetic resources for climate change adaptation: A nutritional analysis of selected best-performing varieties of beans, finger millet and sorghum in Kenya, Tanzania and Uganda - Otieno, Gloria Atieno; Recha, Tobias; Okoth, Judith Kanensi (2020)
The report presents a summary of results from the nutritional analysis conducted on varieties of sorghum, finger millet and beans that were selected by farmers through various rounds of participatory varietal testing and selection on farm and on-station. Best performing varieties were selected based on their drought tolerance, yield, early maturity and resistance to pests and diseases. To compliment this information a further nutritional analysis was done to determine the nutritional content of the varieties specifically those important for nutrition security such as iron, zinc, calcium, and tannins. With this nutrition profiling and agronomic information, relevant stakeholders at all levels, from farmers and breeders, to value-addition sectors and private companies in Kenya, Tanzania and Uganda can now easily select a variety, from among the ones profiled, according to their specific needs for breeding or commercialization.